Chapter Humors, Passions, and Consciousness in Descartes's Physiology: The Reconsideration through the Correspondence with Elisabeth - Muller, Jil (Knowledge and its Histories, 2023)
By pushing Descartes to more clearly explain the union of body and soul beyond the functioning of a 'strong' passion, namely sadness, Elisabeth wants Descartes to review his idea of the passions, and his understanding of the 'theory of the four humors'. This chapter aims at showing that Descartes turns away from Galen's theory of the humors, which he globally adopts in the 1633 Treatise of Man. With the shift in his conceptualization of the humors between this Treatise and the Treatise of the Passions (1649), Descartes analyzed more specifically the inner feelings, consciousness, and the passions, by considering that a man is not simply a body, but a psychophysical being, with a body and a soul.